When sports stood still: Covid-19 and the lost season - Barbie, D. J.; Lamothe, J. C.; Master, S. (COVID-19: Volume II: Social Consequences and Cultural Adaptations, 2020)
The SARS-CoV-2 virus, and the associated COVID-19 pandemic, is perhaps the greatest threat to life, and lifestyles, the world has known in more than a century. The scholarship included here provides critical insights into the institutional responses, communal consequences, cultural adaptations, and social politics that lie at the heart of this pandemic. This volume maps out the ways in which the pandemic has impacted (most often disproportionately) societies, the successes and failures of means used to combat the virus, and the considerations and future possibilities - both positive and negative - that lie ahead. While the pandemic has brought humanity together in some noteworthy ways, it has also laid bare many of the systemic inequalities that lie at the foundation of our global society. This volume is a significant step toward better understanding these impacts.